ProAKAP4 as Novel Molecular Marker of Sperm Quality in Ram: An Integrative Study in Fresh, Cooled and Cryopreserved Sperm - Marta F. Riesco; Luis Anel-Lopez; Marta Neila-Montero; Cristina Palacin-Martinez; Rafael Montes-Garrido; Mercedes Alvarez; Paulino de Paz; Luis Anel (Biomolecules, 2020)
To improve artificial insemination protocols in ovine species it is crucial to optimize sperm quality evaluation after preservation technologies. Emerging technologies based on novel biomolecules and related to redox balance and proteins involved in sperm motility such as ProAKAP4 could be successfully applied in ram sperm evaluation. In this work, a multiparametric analysis of fresh, cooled, and cryopreserved ram sperm was performed at different complexity levels. Samples were evaluated in terms of motility (total motility, progressive motility, and curvilinear velocity), viability, apoptosis, content of reactive oxygen species, oxidation‒reduction potential, and ProAKAP4 expression and concentration. As expected, cryopreserved samples showed a significant decrease of sperm quality (p < 0.05), evidencing different freezability classes among samples that were detected by ProAKAP4 analyses. However, in cooled sperm no differences were found concerning motility, viability, apoptosis, ROS content, and redox balance compared to fresh sperm that could explain the reported decrease in fertility rates. However, although the proportion of sperm ProAKAP4 positive-cells remained unaltered in cooled sperm compared to fresh control, the concentration of this protein significantly decreased (p < 0.05) in cooled samples. This altered protein level could contribute to the decrease in fertility rates of cooled samples detected by some authors. More importantly, ProAKAP4 can be established as a promising diagnostic parameter of sperm quality allowing us to optimize sperm conservation protocols and finally improve artificial insemination in ovine species.